Länsstyrelsernas användning av de allmänna råd som är kopplade till Jordbruksverkets djurskyddsföreskrifter - Westerståhl, Sofia (2020)
Animal welfare is a global issue that affects many people and the development of animal welfare legislation has progressed. Within the EU, there are both animal welfare directives and regulations, and in Sweden, the animal welfare legislation is divided into three parts; the Animal Welfare Act, the Animal Welfare Ordinance and the Swedish Board of Agriculture's (SBA) regulations and general advice. It has previously been shown that the different County Administrative Boards (CAB) have different views on the SBA's regulations and general advice. Some CABs think that the general advices are good and easy to use while others think that it is unclear how they should be used. When updating the regulations, they are also handled differently by SBA and in some regulations the general advices are retained while they are removed in others. In a perfect world, regulations and general advices are used in the same way everywhere and all CABs make uniform assessments and interpretations. This may not be entirely realistic, but in order to promote reasonable coherence, all CABs should feel secure that the regulations and general advices are easy to understand and use in their daily work.